Evaluación de la Concentración de Material Particulado PM10 y PM2.5 en la Parroquia Belisario Quevedo de la Provincia de Cotopaxi en el periodo 2018 – 2019. - Chiluiza Ramirez, Clara Nataly (2019)
The present research project is focused on the determination of the particulate matter present in the environment, the particle size is directly related to its potential to cause health problems. Particles or particulate material can become an important element as a polluting factor in the city environment, it can be deposited on the ground, although it is always dispersed in the air. It is cataloged in the function of its size and in the field of air quality, we talk about PM10 particles that are the largest, which is 10 microns per meter = one millionth of a meter and the fine particles known as and PM 2.5 whose scope would be 2.5 µm with the objective of minimizing the consequences of improving population health and ecosystem quality. The main objective of this research work is to evaluate the concentration of PM10 and PM2.5 particulate material that is generated by industrial vehicles among other human-generated activities existing in the parish to determine the particulate material, the location of two points were determined that are located in the rural area “Galpon Bajo” sector and the urban area in the central sector of the “Belisario Quevedo” Parish, for the monitoring of the particulate matter an E-BAM fine particle sampler was used from the air quality laboratory of the Faculty of Agricultural Sciences and Natural Resources. In the monitoring carried out in the “Belisario Quevedo” parish, values that do not exceed the permissible limits were obtained, the first point is in the rural sector in the “Galpon Bajo” Neighborhood, this point it showed values that are within the maximum permissible limits, a high peak with a value of 27 μg / m3 that is given at 5:00 am this data is in PM10 in PM2.5 a higher peak was obtained at 7:00 am with a value of 19 μg / m3 in some hours we have 0 values this means that the activity of vehicular transport decreases and does not produce a greater percentage of particulate material, in the second point peaks were obtained with values of 51 μg / m3, 41 μg / m3 that occur between 19:00 pm - 20: 00pm at PM 2.5 there was a high peak with a value of 21 μg / m3 at 19:00 pm that were compared with the AIR QUALITY STANDARD BOOK VI ANNEX 4 whose values are within the maximum permissible limits.